Requirements for human natural killer cell development informed by primary immunodeficiency. Issue 6 (December 2016) - Mace, Emily M.
Abstract : Purpose of review: Human natural killer (NK) cell development is poorly understood; however, we gain important insight from cases of human primary immunodeficiency that affect the generation of mature human NK cell subsets. In this review, monogenic primary immunodeficiencies that highlight critical requirements for human NK cell development are discussed. Recent findings: Increased resolution in NK cell phenotyping has revealed NK cell deficiencies that affect the distribution of NK cell subsets found in peripheral blood. These, in addition to those that prevent the generation of mature NK cells, identify important requirements for the maturation and homeostasis of human NK cells. The serious and often life-threatening viral susceptibility that accompanies these highlights the nonredundant role that NK cells play in human health and disease. Summary: Human NK cell deficiency may occur in cases where NK cells are present in normal numbers but subsets are affected.